Measures of excess liquidity - Thorsten Polleit; Dieter Gerdesmeier (HfB - Business School of Finance & Management, 2005)
The aim of this note is to provide an overview of various measures of excess liquidity, which can be defined as the deviation of the actual stock of money from an estimated equilibrium level. Given their dynamic nature, the excess liquidity measures under review are - in the light of long and variable lags of monetary policy - very useful tools to quantify future price pressures. In addition, excess liquidity measures consider inflation as a purely monetary phenomenon: neither the output gap nor liquidity gap - although both form an integral part of the concepts - an be held responsible for inducing a persistent rise in the price level. Despite strong theoretical support, the usefulness of excess liquidity measures depends on the stability of money demand, a question which has of course to be answered in the realm of empirical research.
urn:nbn:de:101:1-20080825168
Keywords: E5; E52; E58; 330; P-star; excess liquidity; monetary policy; ECB